ANALISIS EKONOMI TEBANG PILIH TANAM INDONESIA (TPTI) DAN TEBANG JALUR TANAM INDONESIA (TJTI) DALAM PEMBANGUNAN KEHUTANAN DI LUAR JAWA - B D Nasendi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1996)
Demand side economic analysis or the so called market approach economic analysis was conducted to evaluate the Indonesian Selective Cutting and Planting System (IPTI) and its complementary technique called TJTI (Indonesian Strip Cutting and Planting System) at PT. ITCI (International Timber Corporation Indonesia) Forest Concession Management and Operations in East Kalimantan.The analysis proved that the logs produced and marketed both with TPTI and TJTI systems of forestry operations and practices in East Kalimantan, one of the Indonesian Outer Java Inslands rich tropical forest archipelagoes is viable and economically feasible to maintain the sustainable production and marketing. However, further research is needed to evaluate the resource and supply side economic analysis including sustainable forest resource management, minimum and maximum management unit sizes of both TJTI and TPTI and its sustainability in terms of production, socio-economic and ecological-biophysical.Key words: Economic analysis, TPTI, TJTI and Sustainable Forest Management.